Mitigating information asymmetry in 5G networks - Hermann Bergmann Garcia e Silva; Rúben Manuel Nunes Santos; Manuel Ricardo (Internet Policy Review, 2024)
The implementation of traffic differentiation measures by internet service providers (ISPs) has raised concerns regarding net neutrality, potentially leading to discriminatory practices that challenge existing regulatory frameworks. The complexity of this issue intensifies with the advent of 5G networks as they dynamically assemble elements of the physical infrastructure to create logically segregated domains customised to accommodate usage scenarios with specific requirements, resulting in the categorisation of users, applications, and services into distinct groups which possess the capacity to disrupt the non-discriminatory treatment of data flows. Within this context, a pivotal question arises: how can regulatory authorities effectively evaluate traffic differentiation in 5G networks? In response, this paper proposes an innovative application of the standardised network data analytics function (NWDAF) to facilitate the assessment of internet traffic differentiation. We introduce this novel concept and demonstrate its implementation through a proof-of-concept prototype. By leveraging the NWDAF, regulators may obtain direct and automatic access to performance metrics of 5G networks, enabling the analysis of the traffic management mechanisms employed by ISPs.
Keywords: 300; Internet governance; Net neutrality; 5G; Traffic differentiation; NWDAF